Design And Implementation Of Oranges Sorting System - Muhamad Taufiq Tamam; Arif Johar Taufiq; Wakhyu Dwiono (Universitas Muhammadiyah Purwokerto, 2018)
One application of electronics technology in the field of agriculture is to process the yield of citrus fruits, to choose oranges based on size / dimension. If using manpower (manual) requires high accuracy and takes a long time. By using electronics technology it can be eliminated. The aim of this research is to make prototype of sorting tool that can choose orange fruit based on dimension / size. By using laser sensor and photo diode (photo diode) function to know dimension / size of citrus fruit, citrus fruit will be separated according to dimension / size, big or small. Test results show that this tool can work well in accordance with the planned